Pair term in the electromagnetic current within the Front-Form dynamics: spin-0 case - de Melo, JPBC; Frederico, T.; Pace, E.; Salme, G. (Elsevier B.V., 2002)
The frame and scale dependence of the pair-term contribution to the electromagnetic form factor of a spin-zero composite system of two-fermions is studied within the Light Front. The form factor is evaluated from the plus-component of the current in the Breit frame, using for the first time a nonconstant, symmetric ansatz for the Bethe-Salpeter amplitude. The frame dependence is analyzed by allowing a nonvanishing plus component of the momentum transfer, while the dynamical scale is set by the masses of the constituents and by mass and size of the composite system. A transverse momentum distribution, associated with the Bethe-Salpeter amplitude, is introduced which allows to define strongly and weakly relativistic systems. In particular, for strongly relativistic systems, the pair term vanishes for the Drell-Yan condition, while is dominant for momentum transfer along the light-front direction. For a weakly relativistic system, fitted to the deuteron scale, the pair term is negligible up to momentum transfers of 1 (GeV/c)(2). A comparison with results obtained within the Front-Form Hamiltonian dynamics with a fixed number of constituents is also presented. (C) 2002 Elsevier B.V. B.V. All rights reserved.